Analysis of Sustainable Developmen Goal from the Perspective of Islam - Irwandi, Irwandi; Syafruddin, Syafruddin; Azwar, Welhendi (Islam Realitas: Journal of Islamic and Social Studies, 2024)
The purpose of this article is to discuss the analysis and Sustainable Development Goals from an Islamic perspective, ideology and social ethos. The basis of the debate on sustainable development is to create conditions that balance the needs of present generations with the needs of future generations. Qualitative research methods were used in preparing this article. The type of research carried out is library research using data sources related to the writings of the Ringundan philosophers. Related works include magazines, articles, e-books, etc. The research results show that sustainable development is related to the principles of sustainable development and shows that the concepts developed by experts have their own weight and specificity. Apart from that, these concepts can show a way out of the current global environmental crisis. From an identity perspective, sustainable development cannot be separated from its monotheistic foundation. Sustainable development is still a dilemma for environmental observers, and the analysis carried out shows that the emergence of the concept of sustainable development cannot be separated from modernity and all the problems associated with it. Mapping the concept, sustainable development can be categorized into a constructive postmodernist model.  Tujuan artikel ini adalah untuk membahas analisis dan Tujuan Pembangunan Berkelanjutan dari perspektif Islam, ideologi dan etos sosial. Dasar perdebatan mengenai pembangunan berkelanjutan adalah menciptakan kondisi yang menyeimbangkan kebutuhan generasi sekarang dengan kebutuhan generasi mendatang. Metode penelitian kualitatif digunakan dalam mempersiapkan artikel ini. Jenis penelitian yang dilakukan adalah penelitian kepustakaan dengan menggunakan sumber data yang berkaitan dengan tulisan para filosof Ringundan. Karya-karya terkait antara lain majalah, artikel, e-book, dll. Hasil penelitian menunjukkan bahwa pembangunan berkelanjutan berkaitan dengan prinsip-prinsip pembangunan berkelanjutan dan menunjukkan bahwa konsep-konsep yang dikembangkan oleh para ahli mempunyai bobot dan kekhususan tersendiri. Selain itu, konsep-konsep tersebut dapat menunjukkan jalan keluar dari krisis lingkungan global yang terjadi saat ini. Dari perspektif identitas, pembangunan berkelanjutan tidak dapat dipisahkan dari landasan monoteistiknya. Pembangunan berkelanjutan masih menjadi dilema bagi para pemerhati lingkungan hidup, dan analisis yang dilakukan menunjukkan bahwa munculnya konsep pembangunan berkelanjutan tidak lepas dari modernitas dan segala permasalahan yang terkait dengannya. Memetakan konsepnya, pembangunan berkelanjutan dapat dikategorikan ke dalam model postmodernis yang konstruktif